SISTEM INFORMASI LELANG ONLINE BERBASIS WEB PADA PT. PEGADAIAN CABANG MERUYA (Information Technology and Telematics, 2013)
Abstract -  The  auction  system  of  goods  in  pt. pegadaian meruya branch are still manual, ineffective and closed. Auction organizers still have to offer the product to the   purchaser   by   way contacting   prospective   buyers through  the  phone   one  at  a  time.  However,  with  the information  technology developments that could make the distance, place,  as  well  as  the  speed  of transactions  in business processes is becoming  increasingly easy, author tries to provide solutions by designing ONLINE AUCTION INFORMATION SYSTEM BASED ON WEB AT PT.  PEGADAIAN,  MERUYA  BRANCH  OFFICE.Online auction information system based on web is an application used to support the process of the auction of goods that is to do the bidding price of the auction participants auction based  on  the internet to reach the process of auction transparently and open  to the public. So that the auction process happen more effective and open  to  the public without  having to spread the information manually and  auction participants must not come directly to do the auction bidding. Of this system can be drawn the conclusion  that  the  functionally  of   this  online  auction information system can simplify the process of auctions in PT.  Pawnshops meruya   branch as  the  auction  process media can expand  product sales auctions and accelerate the company's performance in managing the auction sales . Keywords: sistem, sistem informasi, lelang,  lelang online, pegadaian